Developing a feeding assay system for evaluating the insecticidal effect of phytochemicals on Helicoverpa armigera - Mohite, Sharada D.; Patil, Yogita P.; Nichit, Vikram J.; Joshi, Rakesh S. (Jove-Journal of Visualized Experiments, 2023)
Helicoverpa armigera, a lepidopteran insect, is a polyphagous pest with a worldwide distribution. This herbivorous insect is a threat to plants and agricultural productivity. In response, plants produce several phytochemicals that negatively impact the insect's growth and survival. This protocol demonstrates an obligate feeding assay method to evaluate the effect of a phytochemical (quercetin) on insect growth, development, and survival. Under controlled conditions, the neonates were maintained until the second instar on a pre-defined artificial diet. These second-instar larvae were allowed to feed on a control and quercetin-containing artificial diet for 10 days. The insects' body weight, developmental stage, frass weight, and mortality were recorded on alternate days. The change in body weight, the difference in feeding pattern, and developmental phenotypes were evaluated throughout the assay time. The described obligatory feeding assay simulates a natural mode of ingestion and can be scaled up to a large number of insects. It permits one to analyze phytochemicals' effect on the growth dynamics, developmental transition, and overall fitness of H. armigera. Furthermore, this setup can also be utilized to evaluate alterations in nutritional parameters and digestive physiology processes. This article provides a detailed methodology for feeding assay systems, which may have applications in toxicological studies, insecticidal molecule screening, and understanding chemical effects in plant-insect interactions.

Inhibition of trehalose synthesis in lepidoptera reduces larval fitness - Tellis, Meenakshi B.; Mohite, Sharada D.; Nair, Vineetkumar S.; Chaudhari, Bhagyashri Y.; Ahmed, Shadab; Kotkar, Hemlata M.; Joshi, Rakesh S. (Advanced Biology, 2024)
Trehalose is synthesized in insects through the trehalose 6-phosphate synthase and phosphatase (TPS/TPP) pathway. TPP dephosphorylates trehalose 6-phosphate to release trehalose. Trehalose is involved in metamorphosis, but its relation with body weight, size, and developmental timing is unexplored. The expression and activity of TPS/TPP fluctuate depending on trehalose demand. Thus, TPS/TPP inhibition can highlight the significance of trehalose in insect physiology. TPS/TPP transcript levels are elevated in the pre-pupal and pupal stages in Helicoverpa armigera. The inhibition of recombinantly expressed TPP by N-(phenylthio)phthalimide (NPP), is validated by in vitro assays. In vivo inhibition of trehalose synthesis reduces larval weight and size, hampers metamorphosis, and reduces its overall fitness. Insufficient trehalose leads to a shift in glucose flux, reduced energy, and dysregulated fatty acid oxidation. Metabolomics reaffirms the depletion of trehalose, glucose, glucose 6-phosphate, and suppressed tricarboxylic acid cycle. Reduced trehalose hampers the energy level affecting larval vitality. Through trehalose synthesis inhibition, the importance of trehalose in insect physiology and development is investigated. Also, in two other lepidopterans, TPP inhibition impedes physiology and survival. NPP is also found to be effective as an insecticidal formulation. Overall, trehalose levels affect the larval size, weight, and metabolic homeostasis for larval-pupal transition in lepidoptera. Inhibition of trehalose synthesis enzyme TPS/TPP is a good model to study the contribution of trehalose in attaining body weight and in larval-pupal transition. Transcriptomics and metabolomics studies reveal overall reduced energy and dysregulated glucose, protein, and fatty acid metabolism.image
Keywords: Lepidoptera; metabolic homeostasis; trehalose; trehalose 6-phosphate phosphatase